(untitled) (International Journal of Engineering and Computer Science, 2015)
A classical PID controller tuning method for the integrating processes is presented to provide the desired phase margin which acts as the major tuning parameter along with the crossover frequency. Analytical expressions are given for controller setting based on Mikhalevich method. This method provides a way to select the desired phase margin. This method has been tested successfully and compared with the various examples on the basis of integral performance index (ISE and IAE ) to show the effectiveness.